THE EFFECT OF WATER AND FO2 ON THE FERRIC-FERROUS RATIO OF SILICIC MELTS - Gaillard F.; Scaillet B.; Pichavant M.; Beny J.M. (My University, 2001)
New experiments on the effect of dissolved water on the ferric-ferrous ratio of silicic melts have been performed at 200 MPa, between 800°C and 1000°C and for fO2 between NNO-1.35 and NNO+6.6. Water-saturated conditions were investigated. Compositions studied include six metaluminous synthetic melts, with FeOtot progressively increasing from 0.47 to 4.25 wt.%, two natural obsidian glasses (one peraluminous and the other peralkaline) and a synthetic rhyolitic glass having the composition of the matrix glass of the June 15, 1991 Pinatubo dacite. Ferrous iron was analyzed by titration and FeOtot by electron microprobe. Variation of quench rate was found to have no detectable effect on the ferric-ferrous ratio of the hydrous silicic melts investigated. At NNO, no dependence of the ferric-ferrous ratio with temperature is observed. At fO2<NNO+1, metaluminous melts have ferric-ferrous ratios higher than calculated from the Kress and Carmichael (KC) (Kress, V.C., Carmichael, I.S.E., 1991. The compressibility of silicate liquids containing Fe2O3 and the effect of composition: temperature: oxygen fugacity and pressure on their redox states. Contrib. Mineral. Petrol. 108, 82-92.) empirical equation (i.e., water has an oxidizing effect relative to KC), whereas at fO2>NNO+1, the experimental ferric-ferrous ratios are equal or lower than calculated. The peralkaline samples show the same type of behaviour. A non-linear relationship between XFe2O3/XFeO and fO2 implies that a term for dissolved water must be added to the KC equation if it is to be applied to the calculation of ferric-ferrous ratios of hydrous silicic melts. Above NNO+1, the ferric-ferrous ratio is essentially controlled by the anhydrous melt composition and fO2. However, differences exist between measured and calculated ferric-ferrous ratios of silicic melts that are not all attributable to the effect of dissolved water. Additional work is needed to describe more precisely the dependence of the ferric-ferrous ratio on anhydrous melt composition. The oxidizing effect of water is restricted to relatively reduced magmatic liquids. In oxidized calk-alkaline magma series, the presence of dissolved water will not largely influence melt ferric-ferrous ratios.
Keywords: IRON; WATER; OXYGEN FUGACITY; SILICIC MELTS